Eksplorasi Pemanfaatan Aplikasi Keuangan Digital dalam Penyusunan Laporan Keuangan oleh Pelaku UMKM Muda - Sri Rahayu Saputri; Syahraeni; Multi Arnilasari; Masyhuri (Journal of Islamic Economic Studies, 2025)
This study aims to examine the utilization of digital financial applications in the preparation of financial statements by young Micro, Small and Medium Enterprises (MSMEs). The background of the study stems from the crucial role of accurate and well-documented financial reporting as a foundation for sustainable business decision-making. In line with the growing adoption of information technology, various digital financial applications have emerged, offering simplified transaction recording and financial statement preparation. Using a literature review method, this study analyzes relevant sources, including scientific journals, official reports, and recent digital publications, to gain a comprehensive understanding of the effectiveness and challenges of implementing digital financial tools among young MSMEs. . The findings reveal that digital financial applications contribute positively to improving efficiency, orderliness, and transparency in MSMEs’ financial reporting. However, issues such as limited digital literacy and basic accounting knowledge still pose challenges. This study is expected to serve as a conceptual basis for developing digital financial education and assistance policies for young MSMEs in the future.